Institutional Reform in Sustainable Livestock Systems: Resource Management and Development Strategies in the Adaptive Era - Diana Magfiroh (Livestock Science & Innovation Journal, 2025)
Livestock institutions are fundamental to advancing a sustainable livestock sector, especially amidst the challenges posed by climate change and digital transformation. Despite their importance, many smallholder livestock institutions remain formal and have yet to fully optimize their management and developmental functions. This study addresses this gap by exploring how institutional structures and strategies can enhance resilience and productivity. Specifically, it aims to: (1) analyze the structure and function of livestock institutions supporting sustainability, (2) evaluate the effectiveness of HR management and development strategies, and (3) develop an adaptive reform model to respond to socio-ecological dynamics. Unlike previous research, this study uniquely combines a case study approach across three diverse provinces—Yogyakarta, West Java, and West Nusa Tenggara—to capture contextual variations. Employing qualitative methods, data were collected through interviews, observations, and documentation, then thematically analyzed to identify patterns in management and institutional dynamics. Findings reveal that active, structured institutions with data-driven management and cross-sector partnerships significantly improve livestock productivity and resilience. Based on these insights, an adaptive institutional model is proposed, emphasizing functional structure, performance management, and multisector collaboration. The study underscores that institutional reform is vital for fostering inclusive, efficient, and resilient livestock development in a rapidly changing environment.